If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + -2) + -7(x + -4) = 6 + -3 Reorder the terms: 6(-2 + x) + -7(x + -4) = 6 + -3 (-2 * 6 + x * 6) + -7(x + -4) = 6 + -3 (-12 + 6x) + -7(x + -4) = 6 + -3 Reorder the terms: -12 + 6x + -7(-4 + x) = 6 + -3 -12 + 6x + (-4 * -7 + x * -7) = 6 + -3 -12 + 6x + (28 + -7x) = 6 + -3 Reorder the terms: -12 + 28 + 6x + -7x = 6 + -3 Combine like terms: -12 + 28 = 16 16 + 6x + -7x = 6 + -3 Combine like terms: 6x + -7x = -1x 16 + -1x = 6 + -3 Combine like terms: 6 + -3 = 3 16 + -1x = 3 Solving 16 + -1x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + -1x = 3 + -16 Combine like terms: 16 + -16 = 0 0 + -1x = 3 + -16 -1x = 3 + -16 Combine like terms: 3 + -16 = -13 -1x = -13 Divide each side by '-1'. x = 13 Simplifying x = 13
| 6x+4=13+5x | | -5x-8x=26 | | -3b+b=10 | | -b+b=10 | | 3x+5=2+6x | | 5x+3x-5=3 | | 4logx=8 | | ln(x^2)-2lnx=0 | | 2x*(x-4y)= | | cos(0.5x)=0.5 | | t^3-12t^2+36t-30=0 | | 12c+12y=36 | | 0.4+42= | | 42-6x=24 | | P=2c+xforc | | 227=146v | | log(3)(6x-2)=4 | | 7-4(w-2)w= | | 2y+y=25 | | 2x+4y+0.25z=100solve | | 6m=1500 | | 0.5x+402=5.9 | | 14y^3+8y^2+7y+4=0 | | 180*y+4050*x=22000 | | 4050*x+180*y=22000 | | 5n+3n=-2(1-7n) | | 84=u/3 | | 12000(2+7)= | | -3y-7.8=9.6 | | 1.35-0.72x+.12x^2= | | 0.05x+2=0 | | 0.075x^2+4x+1000=0 |